The effect of AIDS peer health education on knowledge, attitudes, and practices of secondary school students in Khartoum, Sudan - Maha Hamad Mohammed Ali; Osman Babiker Osman; Mohamed AE. M. Ibrahim; Waled Amen Mohammed Ahmed (AIMS Press, 2015)
Background: Peer education seeks to enroll students in persuasive communication programs aiming at AIDS prevention. Providing information about AIDS prevention methods can lead to behavioral change and also a potential reduction in unsafe sexual behavior, particularly among young people. Objective: This study aims to assess the role of peer education interventions in improving awareness, attitudes, and practices of secondary school students and peer educators towards AIDS. Methods: This is a pre-and post-study. The study was conducted among 400 students who were randomly selected from 10 gender-balanced schools. They received the information from trained peer educators. 200 peers carried out the intervention (20 peers from each school), which was conducted in phases. The intervention required coordinating with official concerned stakeholders, preparing teaching aids, and four days of training workshops for the peer educators. The data was analyzed using the Statistical Package for Social Science program (SPSS). A paired sample t-test was obtained and utilized to interpret the changes observed in pre- and post-intervention knowledge, attitude, and practice. Results: The study showed that the intervention program improved participants' knowledge from 75.5% to 83.2%. This improvement was with specific regard to the following: the causative agent of AIDs (p = 0.017), which improved from 77.7% to 81.5%; the spread of HIV through mosquitos (p = 0.001), which showed an increase from 12.7% to 23.8%; the program focused on the concept of the HIV carrier (p = 0.001), and also on the AIDS risk when having multiple sex partners, (p = 0.001), showing an increase of 47.5% to 83.5%. Following the knowledge test, the attitudes of students significantly increased from 70% to 83% with regards to youth vulnerability to HIV (p = 0.001), while scored dropped from 15.7% to 8.5% concerning the topic of HIV voluntary testing (p = 0.001). The practices of students changed from 70% to 83% when prompted about shaking the hands of an HIV infected person and also from 84.8% to 87.7% about sharing food with an HIV infected person (p > 0.05). Conclusion: The study concluded that school peer education is an effective approach to inform students of unsafe sexual behavior with regards to HIV/AIDS. It is clear that peer education enables significant improvements to be made with regards to the knowledge, attitudes, and practices of the students.